UJI KEEFEKTIFAN PENGGUNAAN MEDIA PEMBELAJARAN VIDIO ANIMASI “LAYAR HISTORY” MATERI SEJARAH KELAHIRAN PANCASILA PADA PESERTA DIDIK KELAS V SDN KENITEN 1 - Isdela Oktovi Budiawati; Ilmawati Fahmi Imron; Aan Nurfahrudianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted from the results of observations during the Pancasila Education learning, the history of the birth of Pancasila material implemented at SDN Keniten 1. In grade V students there are problems, namely they have difficulty understanding abstract material and the learning outcomes obtained from daily tests are still relatively low or below the Learning Objective Achievement Criteria (KKTP) which is below 75. The purpose of this study was to determine the effectiveness of the animated video learning media "Layar History" on the history of the birth of Pancasila material. The model used in the development carried out in this study is the ADDIE model. The ADDIE model consists of five stages: namely 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. The data analysis technique used was with the research subjects of grade V SDN Keniten 1 as many as 30 students. The results of the effectiveness of the animated video learning media were known through limited trials and extensive trials. Based on the results of limited trials after applying the media with 10 students as subjects, the results obtained were above the predetermined KKTP, which was 75 with a classical completion percentage of 100%. So it can be concluded that the animated video learning media "Layar History" is stated to be very effective for use in small-scale learning processes. Based on the results of extensive trials after applying the media with 20 students as subjects, the results obtained were above the predetermined KKTP, which was 75 with a classical completion percentage of 100%. So it can be concluded that the animated video learning media "Layar History" on the material on the history of the birth of Pancasila is stated to be very effective for use in large-scale learning processes.